Rousettus aegyptiacus Bats Do Not Support Productive Nipah Virus Replication. (4th November 2019) - Seifert, Stephanie N; Letko, Michael C; Bushmaker, Trenton; Laing, Eric D; Saturday, Greg; Meade-White, Kimberly; van Doremalen, Neeltje; Broder, Christopher C; Munster, Vincent J
Abstract: Nipah virus (NiV) is a bat-borne zoonotic pathogen that can cause severe respiratory distress and encephalitis upon spillover into humans. NiV is capable of infecting a broad range of hosts including humans, pigs, ferrets, dogs, cats, hamsters, and at least 2 genera of bats. Little is known about the biology of NiV in the bat reservoir. In this study, we evaluate the potential for the Egyptian fruit bat (EFB), Rousettus aegyptiacus, to serve as a model organism for studying NiV in bats. Our data suggest that NiV does not efficiently replicate in EFBs in vivo. Furthermore, we show no seroconversion against NiV glycoprotein and a lack of viral replication in primary and immortalized EFB-derived cell lines. Our data show that despite using a conserved target for viral entry, NiV replication is limited in some bat species. We conclude that EFBs are not an appropriate organism to model NiV infection or transmission in bats.